Overcoming the cardiac toxicities of cancer therapy immune checkpoint inhibitors - Irabor, Omoruyi Credit; Nelson, Nicolas; Shah, Yash; Niazi, Muneeb Khan; Poiset, Spencer; Storozynsky, Eugene; Singla, Dinender K.; Hooper, Douglas Craig; Lu, Bo (Frontiers in Oncology, 2022)
Cancer immune checkpoint inhibitors (ICIs) have led recent advances in the field of cancer immunotherapy improving overall survival in multiple cancers with abysmal prognoses prior to their introduction. Their remarkable efficacy of ICIs is however limited by their potential for systemic and organ specific immune-related adverse events (irAEs), most of which present with mild to moderate symptoms that can resolve spontaneously, with discontinuation of therapy or glucocorticoid therapy. Cardiac irAEs however are potentially fatal. The understanding of autoimmune cardiotoxicity remains limited due to its rareness. In this paper, we provide an updated review of the literature on the pathologic mechanisms, diagnosis, and management of autoimmune cardiotoxicity resulting from ICIs and their combinations, and provide perspective on potential strategies and ongoing research developments to prevent and mitigate their occurrence.